The Moment of Death in Early Modern Europe, c. 1450-1800
1 online resource (376 pages)
Keywords: Both in our time and in the past, death was one of the most important aspects of anyone’s life. The early modern period saw drastic changes in rites of death, burials and commemoration. One particularly fruitful avenue of research is not to focus on death in general, but the moment of death specifically. This volume investigates this transitionary moment between life and death. In many cases, this was a death on a deathbed, but it also included the scaffold, battlefield or death in the streets. Contributors include: Friedrich J. Becher, Benedikt Brunner, Isabel Casteels, Martin Christ, Louise Deschryver, Irene Dingel, Michaël Green, Vanessa Harding, Sigrun Haude, Vera Henkelmann, Imke Lichterfeld, Erik Seeman, Elizabeth Tingle, and Hillard von Thiessen